The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/ajmg.b.31043
|View full text |Cite
|
Sign up to set email alerts
|

Association and interaction analysis of variants in CHRNA5/CHRNA3/CHRNB4 gene cluster with nicotine dependence in African and European Americans

Abstract: Several previous genome-wide and targeted association studies revealed that variants in the CHRNA5-CHRNA3-CHRNB4 (CHRNA5/A3/B4) gene cluster on chromosome 15 that encode the α5, α3 and β4 subunits of the nicotinic acetylcholine receptor (nAChRs) are associated with nicotine dependence (ND) in European Americans (EAs) or others of European origin. Considering the distinct linkage disequilibrium patterns in European and other ethnic populations such as African Americans (AAs), it would be interesting to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 68 publications
3
49
2
1
Order By: Relevance
“…In addition, within cluster interactions of several SNPs, all located within or flanking CHRNA5-CHRNA3 region, were associated with smoking phenotypes (Li et al, 2010). Here, we have found that an additional 3 0 UTR SNP, rs660652, is associated with ND due to interaction with another gene (COMT), but is not associated to the phenotype directly as are the other two SNP groups.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, within cluster interactions of several SNPs, all located within or flanking CHRNA5-CHRNA3 region, were associated with smoking phenotypes (Li et al, 2010). Here, we have found that an additional 3 0 UTR SNP, rs660652, is associated with ND due to interaction with another gene (COMT), but is not associated to the phenotype directly as are the other two SNP groups.…”
Section: Discussionmentioning
confidence: 58%
“…472). Recent candidate gene association studies (Baker et al, 2009;Bergen et al, 2009;Bierut et al, 2008;Breitling et al, 2009a, b;Chen et al, 2008Chen et al, , 2009Etter et al, 2009;Freathy et al, 2009;Greenbaum et al, 2006;Hoft et al, 2009;Keskitalo et al, 2009;Le Marchand et al, 2008;Li et al, , 2009Perkins et al, 2008aPerkins et al, , b, 2009Philibert et al, 2009;Rigbi et al, 2008;Saccone et al, 2009a, b;Sherva et al, 2008;Spitz et al, 2008;Stevens et al, 2008;Wang et al, 2009;Weiss et al, 2008), and genome-wide association scans (GWASs) (Drgon et al, 2009a, b;Liu et al, 2010Liu et al, , 2009TAG, 2010;Thorgeirsson et al, 2008Thorgeirsson et al, , 2010, with many published candidate gene and GWAS studies through 2009 referenced by Wang and Li (2010), have searched for, and, at varying levels of significance, identified, common variants associated with measures of response to tobacco, tobacco consumption, nicotine dependence, nicotine metabolism, or smoking cessation. However, most of the attributable fraction assumed to be due to heredity cannot be explained by these common single-nucleotide polymorphisms (SNPs), suggesting that rare variants in candidate genes, ie, those with minor allele frequencies (MAFs) substantially o5%, may also contribute to complex disease (Bodmer and Bonilla, 2008;Frazer et al, 2009;Schork et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An association between variation at these loci and risk for lung cancer has also been reported (Thorgeirsson et al, 2008;Hung et al, 2008). Although initial studies were conducted in subjects of mainly European descent, more recent studies have confirmed associations between variation within the CHRNA5/A3/B4 gene cluster and ND-related phenotypes in African-American Li et al, 2009) and Asian populations (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 84%
“…Linkage studies (Li, 2008), candidate-gene association studies, and more recently genome-wide association studies (GWAS) have been used to identify genes associated with ND. The most remarkable results from GWAS and follow-up candidate-gene studies implicate a gene cluster on chromosome 15q.24-15q25 containing CHRNA5, CHRNA4, and CHRNB4, which respectively encode a5, a3, and b4 subunits of the nicotinic acetylcholine receptors (Bierut et al, , 2009Stevens et al, 2008;Saccone et al, 2007;Li et al, 2009;Thorgeirsson et al, 2008;Hung et al, 2008;Berrettini et al, 2008;Weiss et al, 2008). Associations between these genes and ND have been replicated using several different measures of ND.…”
Section: Introductionmentioning
confidence: 99%